2021
DOI: 10.3389/fimmu.2021.645100
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine Inhibits Macrophage Activation and Attenuates Renal Fibrosis After Ischemia-Reperfusion Injury

Abstract: Chronic kidney disease (CKD), which is associated with high morbidity, remains a worldwide health concern, while effective therapies remain limited. Hydroxychloroquine (HCQ), which mainly targets toll-like receptor-7 (TLR-7) and TLR-9, is associated with a lower risk of incident CKD. Taking into account that TLR-9 is involved in the development of renal fibrosis and serves as a potential therapy target for CKD, we investigated whether HCQ could attenuate CKD via TLR-9 signal pathway. The effects of HCQ on rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…In S-100-treated AIH mice, oral administration of 10 or 20 mg/kg HCQ, which referred to the report ( Zheng et al, 2021 ), for 2°weeks markedly diminished the extent of AIH with the loss of liver architecture, congestion, lymphocytic infiltration and large area necrosis (arrows represent inflammatory infiltrations) ( Figure 1A ). We focused on inflammatory cell related markers, such as mature macrophages cell marker F4/80 and lymphocyte marker CD3 to investigate the alleviating effect of HCQ on the inflammatory infiltration of AIH.…”
Section: Resultssupporting
confidence: 70%
“…In S-100-treated AIH mice, oral administration of 10 or 20 mg/kg HCQ, which referred to the report ( Zheng et al, 2021 ), for 2°weeks markedly diminished the extent of AIH with the loss of liver architecture, congestion, lymphocytic infiltration and large area necrosis (arrows represent inflammatory infiltrations) ( Figure 1A ). We focused on inflammatory cell related markers, such as mature macrophages cell marker F4/80 and lymphocyte marker CD3 to investigate the alleviating effect of HCQ on the inflammatory infiltration of AIH.…”
Section: Resultssupporting
confidence: 70%
“…However, the expression of TRPV1, apoptotic, and anti-apoptotic markers was modulated in the cells after treatment with HCQ. Similar to the current results, the protective action of HCQ on the acute INF-induced apoptosis was reported in mice macrophages [50]. In the lymphocytes…”
Section: Discussionsupporting
confidence: 92%
“…Studies of various scientists have shown that aldosterone, through mineralocorticoid signaling, plays a key role in the pathogenesis of ischemia-reperfusion kidney damage, manifested in the development of progressive renal dysfunction, proteinuria, glomerulosclerosis, tubulointerstitial fibrosis, etc. [2,3,5]. According to Barba-Navarro R. I. blockage of mineralocorticoid receptors with spironolactone before or even after ischemia prevents acute functional and structural damage caused by ischemia-reperfusion [6].…”
Section: Discussionmentioning
confidence: 99%
“…The kidney is an organ that is very sensitive to hemodynamic disorders and ischemia [3]. Therefore, the study of the reaction of resistance to hypoxia after ischemia-reperfusion disorders is an urgent issue.…”
mentioning
confidence: 99%